Haploinsufficiency of the Attention-Deficit/Hyperactivity Disorder Risk Gene St3gal3 in Mice Causes Alterations in Cognition and Expression of Genes Involved in Myelination and Sialylation - Rivero, Olga; Alhama-Riba, Judit; Ku, Hsing-Ping; Fischer, Matthias; Ortega, Gabriela; Álmos, Péter; Diouf, David; van den Hove, Daniel; Lesch, Klaus-Peter (Frontiers in Genetics, 2021)
Genome wide association meta-analysis identified ST3GAL3, a gene encoding the beta-galactosidase-alpha-2,3-sialyltransferase-III, as a risk gene for attention-deficit/hyperactivity disorder (ADHD). Although loss-of-function mutations in ST3GAL3 are implicated in nonsyndromic autosomal recessive intellectual disability (NSARID) and West syndrome, the impact of ST3GAL3 haploinsufficiency on brain function and the pathophysiology of neurodevelopmental disorders, such as ADHD, is unknown. Since St3gal3 null mutant mice display severe developmental delay and neurological deficits, we investigated the effects of partial inactivation of St3gal3 in heterozygous (HET) knockout (St3gal3+/-) mice on behavior as well as expression of markers linked to myelination processes and sialylation pathways. Our results reveal that male St3gal3 HET mice display cognitive deficits, while female HET animals show increased activity, as well as increased cognitive control, compared to their wildtype littermates. In addition, we observed subtle alterations in the expression of several markers implicated in oligodendrogenesis, myelin formation, and protein sialylation as well as cell adhesion/synaptic target glycoproteins of ST3GAL3 in a brain region- and/or sex-specific manner. Taken together, our findings indicate that haploinsufficiency of ST3GAL3 results in a sex-dependent alteration of cognition, behavior and markers of brain plasticity.